2022
DOI: 10.1590/1982-0275202239e190177
|View full text |Cite
|
Sign up to set email alerts
|

The type of motivation does matter for university preparation

Abstract: Using Self-Determination Theory, the relationship between motivation (autonomous and controlled), academic self-efficacy, test anxiety, life satisfaction and academic achievement was studied in a group of pre-university students from Lima-Peru. A total of 252 students of both sexes with ages between 16 and 30 years (Mage = 17.69) were assessed. Correlational analyses showed the expected relationships among the studied variables. The path analysis performed gave evidence of the fulfillment of the hypotheses pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Controlled motivation is regulated by either external control such as compliance, rewards, or avoiding punishment, or internal control such as self-control, ego-involvement, or attaining self-esteem (Ryan & Deci, 2020). Previous studies show that controlled motivation is negatively correlated with optimal learning indicators such as time management, concentration, and attitude (Vansteenkiste et al, 2005), and positively correlated with dropout intentions (Jeno et al, 2018), surface approaches to learning (Kusurkar et al, 2013), and testanxiety (Iraola-Real et al, 2022). Conversely, while some studies have linked it to negative learning outcomes, others have suggested that controlled motivation may have some energizing effects, which in turn predicts greater achievement (e.g., Botnaru et al, 2021;Jeno et al, 2021).…”
Section: The Correlates Of Basic Psychological Needs and Motivation I...mentioning
confidence: 99%
“…Controlled motivation is regulated by either external control such as compliance, rewards, or avoiding punishment, or internal control such as self-control, ego-involvement, or attaining self-esteem (Ryan & Deci, 2020). Previous studies show that controlled motivation is negatively correlated with optimal learning indicators such as time management, concentration, and attitude (Vansteenkiste et al, 2005), and positively correlated with dropout intentions (Jeno et al, 2018), surface approaches to learning (Kusurkar et al, 2013), and testanxiety (Iraola-Real et al, 2022). Conversely, while some studies have linked it to negative learning outcomes, others have suggested that controlled motivation may have some energizing effects, which in turn predicts greater achievement (e.g., Botnaru et al, 2021;Jeno et al, 2021).…”
Section: The Correlates Of Basic Psychological Needs and Motivation I...mentioning
confidence: 99%